A comparative and comprehensive analysis of perinatal and neonatal death using repeated measurement: A Malaysia case study - Mustafa, Mamat; Wan Muhamad Amir, Wan Ahmad; Nor Azlida, Aleng (2014)
The case of perinatal and neonatal death is becoming a serious case. The incident of neonatal and perinatal death has increased dramatically in the last decade. Increasing case of neonatal and perinatal death had worried to the most of pregnant women all over the world. A large numbers of children die soon after the mother gives birth (during the first four weeks) which is better known as neonatal death or during pregnancy time (death of a fetus). A repeated measure analysis was conducted on two different types of data in order to determine the significance different level between of these two groups. Data collection consist of the 13 states in Malaysia and classified into two groups. Group one is the number of neonatal death case since 2001 till 2011 and Group Two is the number of perinatal death case since 2001 till 2011. In this study, we compared all the possible the gained results from perinatal death and neonatal death and come out with some suggestion and conclusion. Results for the neonatal death Female ( F( .3 174 51, .997) = .4 177, p < 05.0 )) and male ( F ( .3 176 44, .462 ) = .5 440, p < 05.0 )) shows that there are significant difference because it’s less than the criteri on value of α = 05.0 . The mean case of male neonatal death in years can be summarize as follows : year 2001 (70.53 ± 43.00), year 2002(68.13 ± 41.48), year 2003(58.20 ± 40.15), year 2004(68.66 ± 47.50), year 2005(68.93 ± 43.07), year 2006(67.66 ± 38.75), year 2007(64.93 ± 39.14), year 2008(74.33 ± 48.87), year 2009(83.06 ± 55.03), year 2010(81.00 ± 52.85) and year 2011(79.13 ± 47.85). The mean case of female neonatal death in years can be summarize as follows : year 2001 (53.87 ± 34.47), year 2002(54.93 ± 32.06), year 2003(44.46 ± 30.27), year 2004(49.2667 ± 33.42896), year 2005(51.80 ± 34.37), year 2006(48.200 ± 30.40), year 2007(53.60 ± 34.03), year 2008(53.80 ± 35.19), year 2009(59.93 ± 36.94), year 2010(58.66 ± 36.19) and year 2011(59.2000 ± 42.52). Results for the perinatal death ( F ( .2 597 36.351) = .2 547, p > 05.0 )) and male ( F( .1 972 27, .605) = .1 065, p > 05.0 )) shows that there are no significant difference from the 2001 to 2011. Finding shows that there was a significant difference between male and female in neonatal death in years while and for the perinatal death there is no significant different between male and female.